Candida auris cells form giant lipid droplets to survive in harsh environments - Qiushi Zheng; Chao Li; Tianren Hu; Jian Bing; Clarissa J. Nobile; Haiqing Chu; Guanghua Huang (Communications Biology)
Abstract The emerging fungal pathogen Candida auris is notorious for environmental persistence, which is a major contributor to outbreaks in healthcare settings. Here we report that giant lipid droplets (gLDs) inside C. auris cells play critical roles in the ability to survive harsh environments. C. auris cells that contain gLDs exhibit an increased tolerance to environmental stresses, antifungals, and host-associated antimicrobial peptides. These cells often undergo significant cell wall remodeling and sloughing of the outer layer of the cell wall. Lipidomics analysis indicates that cells with gLDs contain a significantly higher level of triacylglycerols, sterol esters, and other lipids, such as glycerolipids, sphingolipids, and sterol lipids. At the transcriptional level, a large set of differentially expressed genes was observed between C. auris cells with and without gLDs. Our study reveals that gLDs are a new strategy used by C. auris to adapt to stressful conditions and to persist in hospital environments.